Labor Demand Shocks at Birth and Cognitive Achievement during Childhood - Krishna Regmi; Daniel J. Henderson (Institute of Labor Economics (IZA), 2019)
As epidemiological studies have shown that conditions during gestation and early childhood affect adult health outcomes, we examine the effect of local labor market conditions in the year of birth on cognitive development in childhood. To address the endogeneity of labor market conditions, we construct gender-specific predicted employment growth rates at the state level by interacting an industry's share in a state's employment with the industry's national growth rate. We find that an increase in employment opportunities for men leads to an improvement in children's cognitive achievement as measured by reading and math test scores. Additionally, our estimates show a positive and significant effect of male-specific employment growth on children's Peabody Picture Vocabulary Test scores and in home environment in the year of birth. We find an insignificant positive effect of buoyancy in females' employment opportunities on said test scores.
Keywords: J20; J21; I20; I30; 330; labor market conditions; cognitive ability; child's well-being